Evaluating Sensitivity of the Ranking of Forest Fuel Treatments to Manager’s Risk Attitudes and the Importance of Treatment Objectives, Montana, USA - Tony Prato; Travis Paveglio (International Journal of Forestry Research)
This study develops a conceptual framework for evaluating the sensitivity of the ranking of forest fuel treatment strategies (FTSs) to variation in managers’ risk attitudes and the importance ratings managers assign to fuel treatment objectives and demonstrates the application of the framework using a case study. The conceptual framework involves (1) defining a utility function on an index that is a weighted average of fuel treatment objectives and incorporates a manager’s risk attitude; (2) using the utility function to calculate utility values for FTSs; (3) applying the stochastic efficiency with respect to a function method to utility values to obtain certainty equivalents (CEs); and (4) ranking FTSs based on statistically significant differences in median CEs for pairs of FTSs. The case study involves three (federal, state, and private) forested areas in Flathead County, Montana, USA, three FTSs (i.e., Community Wildfire Protection Plan (CWPP) Priority; CWPP & Wildland-Urban Interface Priority; and No Priority), three treatment objectives (i.e., minimizing expected residential monetary losses from wildfire, minimizing expected deviation of forest ecological conditions from their historic range and variability, and maximizing expected net returns from timber harvesting associated with fuel treatment), two risk attitudes (i.e., almost risk neutral and highly risk averse), and 35 weight scenarios for treatment objectives. Case study results are used to test the hypothesis that the ranking of FTSs is sensitive to manager’s risk attitudes and the importance ratings for management objectives. The ranking of FTSs for the three forested areas was insensitive for an almost risk neutral manager and sensitive for a highly risk averse manager. In general, the case study indicates that the ranking of FTSs is sensitive to both a forest manager’s risk attitudes and the importance ratings assigned to fuel treatment objectives.